Design of E-Library SD Negeri 11 Tanah Garam Kota Solok Based on Web: Perancangan E-Library SD Negeri 11 Tanah Garam Kota Solok Berbasis Web - evi yulia susanti evi (International Journal of Technology Vocational Education and Training, 2020)
Library in Public Elementary school 11 Tanah Garam Solok City quite achievement compared to other school libraries, with this e-library users can make it as a medium of information as well as a library promotion media for Elementary School level in Solok City. Data obtained from library from Public Elementary School 11 Tanah Garam Solok City, then the design of this e-library uses some supporting software, i.e. Bootstrap, PHP, MySQL, Xampp. From the results of this design e-library application makes it easy for library visitors to find the books you want without having to come to the library. Enough with the connection to the library with a computer connected to the internet network. Then with the e-library application it also helps librarians in book collection, visitor data collection.